IMPLEMENTASI PESAN MORAL MISI PROFETIK MUHAMMAD MENURUT FAZLUR RAHMAN - Lukman Hakim; Dani Ramdani (UIN Syarif Hidayatullah Jakarta, 2019)
Abstract. Muhammad's prophetic mission is a mission in an effort to disseminate moral teachings whose roots are found in the teachings of monotheism, as is often emphasized in the Qur'an: efforts to uphold social justice, egalitarianism and protection of the weak. Rahman offers a hermeneutic method to refine the Qur'an and criticize the historical awareness that exists in Muslims. This is done to provide the right meaning for the Qur'an, as well as examine the awareness of the religious traditions of Muslims today. Then Rahman offered the double movement method. This method will be very useful for examining all forms of religious institutionalization established by Muslims today, then confirming it to the time of the Prophet to obtain legitimacy or appropriate reference to religious interpretations. Double movement, intended to provide the right meaning for Muslim efforts to interpret religion based on traditions established by the Prophet: refers to the initial conception that was built by the Prophet and his companions. Abstrak. Misi profetik Muhammad merupakan suatu misi dalam upaya menyebar-luaskan ajaran moral yang muaranya terdapat dalam ajaran monoteisme, sebagaimana yang sering ditegaskan dalam al-Qur’ân: usaha untuk menegakkan keadilan sosial, egaliterianisme dan perlindungan terhadap yang lemah. Rahman menawarkan metode hermeneutika untuk menfasirkan kembali al-Qur’ân dan mengkritisi kesadaran sejarah yang ada dalam umat Islam. Hal ini dilakukan untuk memberikan makna yang tepat bagi al-Qur’ân, sekaligus memeriksa kesadaran tradisi keberagamaan umat Islam masa kini. Kemudian Rahman menawarkan metode double movement. Metode ini akan sangat berguna untuk memeriksa segala bentuk institusionalisasi keberagamaan yang dibangun oleh umat Islam di masa kini, kemudian mengkonfirmasikannya ke masa Nabi untuk mendapatkan legitimasi atau rujukan yang tepat terhadap interpretasi keberagamaan. Double movement, dimaksudkan untuk memberikan makna yang tepat bagi usaha umat Islam untuk melakukan interpretasi keberagamaan berdasarkan tradisi yang dibangun oleh Nabi: merujuk kepada konsepsi awal yang telah dibangun oleh Nabi beserta para sahabatnya.